An improved tool for household faeces management in rural Bangladeshi communities. Issue 7 (5th April 2013) - Sultana, Rebeca; Mondal, Utpal K.; Rimi, Nadia Ali; Unicomb, Leanne; Winch, Peter J.; Nahar, Nazmun; Luby, Stephen P.
Abstract Objective To explore child defecation and faeces management practices in rural Bangladesh with the aim to redesign and pilot a tool to facilitate removal and disposal of faeces. Methods We conducted six group discussions, six short interviews and three observations of practices and designed the new tool. We piloted the new tool and elicited feedback through two in‐depth interviews and two observations. Results Until three years of age, a child commonly defecates in the courtyard and occasionally inside the house. A heavy digging hoe was commonly used to remove child faeces. Mothers preferred a redesigned 'mini‐hoe' and found it easier to use for removal and disposal of liquid faeces. Conclusions Promoting modified local tools may contribute to improving environmental sanitation and health.